Constitutional Implications of Constitutional Court Decision No. 105/PUU-XXII/2024 on Freedom of Expression and Defamation in Indonesia - Majid, Pipit Somefotorono; Sari Angraeni, Besse (IAIN Bone, 2025)
This study examines the constitutional implications of the Constitutional Court Decision No. 105/PUU-XXII/2024 on Indonesia’s digital criminal law system and the urgency of harmonizing the Electronic Information and Transactions Law (UU ITE) with the new Criminal Code (KUHP). The research employs a normative (doctrinal) legal methodology with statutory, case, and conceptual approaches, analyzing positive legal norms, judicial decisions, academic literature, and reports from digital rights monitoring organizations. The analysis focuses on the Court’s interpretation of the term “other person” in Articles 27A and 45 of the UU ITE and the material offense principle in the dissemination of false information (“hoaxes”) under Article 28 of the UU ITE. Findings reveal that the Court restricts the defamation offense to natural persons and requires tangible harm for hoax-related liability, thereby reinforcing the principles of legality, proportionality, and legal certainty. The study underscores the necessity of harmonizing the UU ITE with the new KUHP and other criminal regulations to prevent arbitrary criminalization of public expression and safeguard constitutionally protected freedom of expression. The scholarly contribution lies in formulating a framework for digital criminal law that balances individual reputation protection with freedom of expression while providing an analytical perspective on constitutional interpretation mechanisms in addressing the challenges of digital regulation.